"Ang Ating Iisang Kuwento" our collective story: Migrant Filipino workers and participatory action research. Issue 1 (March 2014) - Francisco, Valerie
Studies that utilize participatory action research (PAR) methods in immigrant communities draw on participatory methods to explore immigrant health and incorporation. Many of these studies have used PAR, mainly, to contact "hard-to-reach" immigrant populations who are ofttimes isolated from research and social services on the basis of language, status, and location. In this paper, I argue that PAR methodology and principles can be maximized in immigrant communities if it asserts migrants' lived experiences as "expertise" on the global institutionalization of migration and low-wage migrant work in the US. I provide data on the Filipino migrant experience and a PAR project with Filipino domestic workers in New York City to show how PAR can capture the systematically organized Philippine labor export policy alongside the individual experience of Filipino immigrants in the US. I discuss kuwentohan, or talk story in Tagalog, and theater as forms of participatory collection and analysis that captures the complex dynamics of migration from macro to micro scales. Lastly, I argue that the political potential of PAR in migrant communities presents itself when migrant workers recount their own experience and begin to understand that those individual stories are part of a larger story of forced migration, labor export policy, and low-wage work. PAR allows for these structural critiques to emerge through the research process.